2020
DOI: 10.4103/jfmpc.jfmpc_719_20
|View full text |Cite
|
Sign up to set email alerts
|

Importance of effective communication during COVID-19 infodemic

Abstract: The impact of COVID-19 on vulnerable groups would rely in part on the quality of communication regarding health risk and danger. Strategic planning should take full account of the way life conditions, cultural values, and risk experience affect actions during a pandemic. Concept of information education communication, Social behaviour change communication, social marketing usually technology and media is recapitulation. Ignorance with sociocultural, economic, psychological, and health factors can jeopardize ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
80
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(93 citation statements)
references
References 6 publications
1
80
0
2
Order By: Relevance
“…The official communication from BC MoH we made available on our website prior to the forum and the health literature from the BC MoH given out at the forum were both translated into traditional Chinese. Seeing their cultural beliefs represented, our participants may have been more likely to feel safe while attending and act on that information [ 21 ]. In fact, given the now well-documented disproportionate amount of burden shared by ethnic minorities with regards to COVID-19, it becomes even more important to emphasize the need for culturally tailored programming when passing on health messages or to promote safe practices when conducting mass gatherings in the future [ 22 - 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The official communication from BC MoH we made available on our website prior to the forum and the health literature from the BC MoH given out at the forum were both translated into traditional Chinese. Seeing their cultural beliefs represented, our participants may have been more likely to feel safe while attending and act on that information [ 21 ]. In fact, given the now well-documented disproportionate amount of burden shared by ethnic minorities with regards to COVID-19, it becomes even more important to emphasize the need for culturally tailored programming when passing on health messages or to promote safe practices when conducting mass gatherings in the future [ 22 - 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…During a pandemic, it is essential that any communicated information is accurate, authoritative, reliable, easy to understand, accessible, leaves little to interpretation, and quickly shuts down any misinformation that can be potentially spread amongst the community. 9 , 10 , 12 , 19 , 20 …”
Section: Introductionmentioning
confidence: 99%
“…In addition, studies investigating responses during the early stages of prior pandemics have identified a number of important demographic, attitudinal, and psychological factors that could influence compliance ( DiGiovanni et al, 2004 ; Bish and Michie, 2010 ; Reddy and Gupta, 2020 ). With respect to demographic factors, evidence from previous and the current COVID-19 pandemic suggest that age is a key factor, with young adults are likely to be least compliant ( Bish and Michie, 2010 ; Barari et al, 2020 ; Everett et al, 2020 ; Pfattheicher et al, 2020 ; YouGov, 2020 ).…”
Section: Introductionmentioning
confidence: 99%